Evaluation of a Telerobotic System for Transnasal Surgery of the Larynx and Airways in Cadavers. (30th April 2014) - Dharamsi, Latif M.; Bajo, Andrea; Netterville, James L.; Garrett, C. Gaelyn; Simaan, Nabil
Abstract : Objectives: Minimally invasive, transnasal endoscopic approaches to the larynx have been utilized but are limited by the precision and accuracy afforded to the surgeon. The objective of this study is to analyze the feasibility of a rapidly deployable telerobotic system for enabling transnasal microsurgery of the larynx and upper airways, specifically injection laryngoplasty. Study Design: This is a feasibility study. Setting: This study was conducted at a laboratory in the Department of Mechanical Engineering at Vanderbilt University. Subjects and Methods: A feasibility study was conducted in which a telerobotic system was transnasally inserted in both a human intubation trainer mannequin and a cadaver. A flexible needle was passed through an instrumentation port and targeted specific areas of the vocal folds of our models to simulate injection laryngoplasty. The experiments were recorded with both still and video photography. Average forces exerted on surrounding tissue and times of deployment were measured. Results: Our robot was able to expeditiously gain access to the glottis with an average manual insertion time of 5.87 seconds while exerting minimal forces on the surrounding tissues with an average force of 4.45 Newtons. The onboard fiberoptic endoscope conveyed images of adequate quality for the completion of a simulated injection medialization laryngoplasty. The experiment was successfully completed in both mannequin and cadaveric models. Conclusion: This telerobotic system proved to be capable of being rapidly deployed to the upper airways while exerting minimal forces to the surrounding structures and successfully simulated injection medialization laryngoplasty.